The profile linguisticphilosophical of the journalistic concept - Ulyanova, Irina (Estudios sobre el Mensaje Periodístico, 2014)
The journalistic conception is incorporated into the pace of philosophy being one of the attributes of its system as an instrument of cognition. Bearing in mind informative and evaluative functions of journalistic genre the most adequate philosophical paradigms (cause and effect, induction and deduction, thesis and antithesis) projected into the sphere of linguistics are used in the article. The Linguistic philosophical integration allows to characterize the journalistic world in two plans: extralinguistic on the basis of real modus of the object and intralinguistic on the basis of conceptual modus of the subject.